2018
DOI: 10.24198/kultivasi.v16i3.14377
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh pola tanam tumpangsari jagung dan kedelai terhadap pertumbuhan dan hasil jagung hibrida dan evaluasi tumpangsari di Arjasari Kabupaten Bandung

Abstract: Maize and soybean are important food after paddy in Indonesia. Maize and soybean consumption increase continually due to population growth. One of the ways to increase crop production can be done by intercropping.Intercropping is a planting system by growing two or more crops simultaneously on the same land in one year. The objectives of this research were to determine appropriate maize hybrid genotype and soybean combinations in intercropping system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
1
3
0
6
Order By: Relevance
“…This showed that yellow sweet corn was genetically more adaptive to all cropping systems (monoculture or intercropping) than purple sweet corn. The results of the intercropping system are in accordance with the research of Yuwariah et.al [17] that corn and IOP Publishing doi:10.1088/1755-1315/1172/1/012006 5 soybeans grown in intercropping gave significant results. It was also in line with the research of Balitkabi [15] that the intercropping of corn and soybeans gives optimal results.…”
Section: Corn -Soybean Growth and Yield Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This showed that yellow sweet corn was genetically more adaptive to all cropping systems (monoculture or intercropping) than purple sweet corn. The results of the intercropping system are in accordance with the research of Yuwariah et.al [17] that corn and IOP Publishing doi:10.1088/1755-1315/1172/1/012006 5 soybeans grown in intercropping gave significant results. It was also in line with the research of Balitkabi [15] that the intercropping of corn and soybeans gives optimal results.…”
Section: Corn -Soybean Growth and Yield Resultssupporting
confidence: 89%
“…The results of the research of Pujiwati [12] and Susilo [13] indicate that the productivity of intercropping rice with other crops is higher than the monoculture system. Potential and prospective intercropping is applied to plants that have complementary effects [14,15,16,17]. Dewi et al [18] proved that sweet corn intercropping treatment with other compatible crops tended to have higher yields than monoculture treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Kedelai dan jagung ialah tanaman pangan utama setelah padi (Yuwariah et al, 2017). Menurut BPS (2022) konsumsi kedelai lokal tahun 2022 mencapai 2,32 juta ton.…”
Section: Pendahuluanunclassified
“…Pola jagung monokultur dan tumpangsari jagung + bayam, jagung + buncis, jagung + kacang tanah mampu menghasilkan jumlah daun tertinggi pada seluruh waktu pengamatan. Menurut Yuwariah et al (2017), pada pola tumpangsari tanaman jagung dan kedelai, tanaman jagung lebih unggul dalam persaingan menyerap air, unsur hara, cahaya dan pertumbuhan akar. Persaingan antar jenis tanaman maupun antar individu satu dengan individu lainnya pada satu jenis tanaman merupakan salah satu faktor yang mempengaruhi pertumbuhan tanaman dalam sistim tumpangsari dalam perebutan unsur-unsur hara, air, dan cahaya sehingga pertumbuhan dan perkembangan tanaman menjadi rendah atau terhambat pada tanaman yang kalah bersaing.…”
Section: Jumlah Daununclassified